Long-term effect of natalizumab in patients with RRMS: TYSTEN cohort. (April 2021) - Bigaut, Kévin; Fabacher, Thibaut; Kremer, Laurent; Ongagna, Jean-Claude; Kwiatkowski, Arnaud; Sellal, François; Ferriby, Didier; Courtois, Sylvie; Vermersch, Patrick; Collongues, Nicolas; Zéphir, Hélène; De Seze, Jérôme; et al.
Background: Data are needed on long-term effect of natalizumab (NTZ) in relapsing-remitting multiple sclerosis (RRMS). Objectives: To evaluate the time of onset of secondary progressive phase in patients with an RRMS treated with NTZ and to investigate predictive factors. Methods: TYSTEN is an observational study. Patients starting NTZ between 2007 and 2012 were included and followed up until October 2018. Relapses, Expanded Disability Status Scale (EDSS) scores, and results of brain magnetic resonance imaging (MRI) were collected each year. Data were used to estimate the cumulative probability of several poor outcomes such as secondary progressive multiple sclerosis (SPMS) conversion, EDSS worsening, EDSS 4.0, and EDSS 6.0. Results: 770 patients were included. The mean follow-up duration was 97 months and the mean time exposure to NTZ was 66 months. At 10 years, the cumulative probability of SPMS was 27.7%. Predictive factors for poor outcomes were a ⩾1-point increase in EDSS score from baseline, new T2 lesion or T1 gadolinium-enhancing lesion, the occurrence of relapse at 1 or 2 years and No Evidence of Disease Activity (NEDA-3; no relapse, no new T2 or T1 gadolinium-enhancing lesions, no progression) was a protective factor. Conclusion: In our cohort of patients treated with NTZ, poor outcomes were infrequent and are driven by disease activity.